The relationship between carotid and coronary calcification in patients with coronary artery disease. (26th February 2021) - Shenouda, Rafik; Vancheri, Sergio; Maria Bassi, Emilio; Nicoll, Rachel; Sobhi, Mohammed; El Sharkawy, Eman; Wester, Per; Vancheri, Federico; Henein, Michael Y.
Abstract: Background: Atherosclerosis is a multi‐system pathology with heterogeneous involvement. We aimed to investigate the relationship between the presence and severity of carotid and coronary calcification in a group of patients with coronary artery disease. Methods: Sixty‐three patients presenting with unstable angina or positive stress test for myocardial ischaemia were enrolled in this study. All patients underwent CT scanning of the carotid and coronary arteries using the conventional protocol and Agatston scoring system. Risk factors for atherosclerosis were also analyzed for correlation with the extent of arterial calcification. Results: Total coronary artery calcium score (CAC) was several times higher than total carotid calcium score (1274 (1018) vs 6 (124), p = 0·0001, respectively). The left carotid calcium score correlated strongly with the right carotid calcium score (rho = 0·69, p < 0·0001). The total CAC score correlated modestly with the total carotid calcium score (rho = 0·34, p = 0·007), in particular with left carotid score (rho = 0·38, p = 0·002), but not with the right carotid score. The left coronary calcium score correlated with the right coronary calcium score (rho = 0·35, p = 0·004), left carotid calcium score (rho = 0·33, p = 0·007) and left carotid calcium score at the bifurcation (rho = 0·34, p = 0·006). While hypertension correlated with carotid calcium score, diabetes and dyslipidaemia correlated with left CAC score. Conclusion: In patients with coronary disease, the carotid calcification pattern appeared to be similar between the right and left system in contrast to that of the coronary arteries. CAC correlated only modestly with the carotid score, despite being significantly higher. Hypertension was related to carotid calcium score while diabetes and dyslipidaemia correlated with coronary calcification.